2022
DOI: 10.1039/d2gc02608b
|View full text |Cite
|
Sign up to set email alerts
|

Short-process synthetic strategies of sustainable isohexide-based polyesters towards higher molecular weight and commercial applicability

Abstract: Isohexides (1,4:3,6-dianhydrohexitols) represent a family of bio-based heterocyclic diols attracting over 40 years’ attention from both industry and academia. Their unique properties, including high structural rigidity, high hydrophilicity and distinct...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 170 publications
(323 reference statements)
0
7
0
Order By: Relevance
“…We presumed that isosorbide undergoes degradation during the reaction leading to volatile by-products that could not be detected by NMR. 31,32 Indeed, a difficult balance was again found between selective functionalization and degradation pathways. To decrease the functional complexity of the substrate and to understand the formation of side products, exomonobenzylated isosorbide 1 was then considered as a model substrate (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We presumed that isosorbide undergoes degradation during the reaction leading to volatile by-products that could not be detected by NMR. 31,32 Indeed, a difficult balance was again found between selective functionalization and degradation pathways. To decrease the functional complexity of the substrate and to understand the formation of side products, exomonobenzylated isosorbide 1 was then considered as a model substrate (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…This type of degradation was already reported under acidic conditions, indicating once again the selectivity challenge in functionalizing this substrate. 31,34 The cutting edge issue was to find the appropriate balance between conversion and degradation/selectivity on a substrate that is difficult to handle. The use of other strong bases such as KOH or KHMDS led to the same conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of melting behaviors, the melting peaks of the copolyesters were 10–15 °C lower than those of homopolyesters. When the bioderived monomers, that replace the terephthalates, had bulky and asymmetric molecular structures, crystallizations of the terephthalate units were hindered by chain packing. , The melting temperatures were typically decreased and broadened with increases of the bioderivated units and, when the contents were greater than 30–40%, most of the copolyesters exhibited amorphous characteristics (Figure S8b). Also, the Ct-diester incorporated PET copolyesters showed decreases in T m with increase of the incorporated ratio .…”
Section: Resultsmentioning
confidence: 99%
“…It has gained more attention and emerged as an renewable comonomer for high-performance polymeric materials . When the highly rigid bicyclic asymmetric structure of the IS building block is incorporated into the polymer, it dramatically enhances the T g of the materials. The comonomer feed ratios were adjusted in each case to produce PESF copolymers with T g in the range of PET. The studies demonstrated that the incorporation of FDCA, BFDCA, or IS into PESF resulted in copolyesters with significantly enhanced T g values, which makes the reported copolyesters potentially more suitable for manufacturing heat-resistant drink bottles or food packaging materials than PESF.…”
Section: Introductionmentioning
confidence: 99%